Oracle E-business suite R12 supply chain management : drive your supply chain processes with Oracle E-business suite R12 supply chain management to achieve measurable business gains /: drive your supply chain processes with Oracle E-business suite R12 supply chain management to achieve measurable business gains. (2010) - Unknown
No abstract available